2022
DOI: 10.3390/w15010004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impacts of Phyto-Remediation on Water Quality of the Litani River by Means of Two Wetland Plants (Sparganium erectum and Phragmites australis)

Abstract: Water pollution from human activities is largely a result of the discharge of wastewater and industrial waste into rivers. Phytoremediation, the technique that uses plants to remove pollutants from the polluted waters, is a growing field of research because of its various environmental advantages. This study aims to evaluate the efficiency of a constructed wetland in removing pollutants and treating the polluted waters of the Litani River in Lebanon, by means of two aquatic plants, Phragmites australis and Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…According to the Brazilian regulation ABNT 13969/97, the treated effluent could be reused to wash floors and pavements and irrigate gardens and landscapes. In systems involving largescale (35,000 m 2 ) SCW without microalgae, results revealed that there was an increase in the sulfate concentration (SO 4 −2 ) [53]. Such an increase might be due to the denitrifying bacteria activity, since chemolithoautotrophic bacteria reduce nitrate, while the S-oxidant bacteria oxidize sulfide to return SO 4 −2 during denitrification.…”
Section: Use Of Microalgae In Scw To Improve the Effluent Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Brazilian regulation ABNT 13969/97, the treated effluent could be reused to wash floors and pavements and irrigate gardens and landscapes. In systems involving largescale (35,000 m 2 ) SCW without microalgae, results revealed that there was an increase in the sulfate concentration (SO 4 −2 ) [53]. Such an increase might be due to the denitrifying bacteria activity, since chemolithoautotrophic bacteria reduce nitrate, while the S-oxidant bacteria oxidize sulfide to return SO 4 −2 during denitrification.…”
Section: Use Of Microalgae In Scw To Improve the Effluent Qualitymentioning
confidence: 99%
“…Such an increase might be due to the denitrifying bacteria activity, since chemolithoautotrophic bacteria reduce nitrate, while the S-oxidant bacteria oxidize sulfide to return SO 4 −2 during denitrification. This bacterial activity might explain the high NO −3 removal and the SO 4 −2 release in CW, which requires post-treatment so that the effluent can be reused [53].…”
Section: Use Of Microalgae In Scw To Improve the Effluent Qualitymentioning
confidence: 99%
“…Water hyacinth exposed to Cu(II) 50 ppm in the contaminated water were subjected to the 30-day phytoremediation after coming into contact with water. Atomic Absorption Spectrophotometer (AAS) was used to measure the amount of zinc in the sample 4 times at 10-day intervals [11].…”
Section: Examination Of Copper Levels In Lake Tempe Water and Water H...mentioning
confidence: 99%